IOT based real-time ECG monitoring of rural cardiac patients - Ramu, R; Dr. A. Sukesh Kumar, Prof. (International Journal of Engineering and Technology, 2018)
According to the census in India, about 83 crores people live in rural area out of 121 crores total population. Patients living in these rural area mainly depends on Primary Health Centre (PHC). Due to insufficient and low facility health care center in rural area in India, patients have to depend on nearby cities to get proper treatment. With the help of new technologies such as wireless communication and Internet of Things (IoT) we can improve the health care requirements of rural cardiac patients. In this work, a telemedicine application for online moni-toring and analysis of cardiac patient is implemented. A low cost high quality wireless ECG monitoring system based on IoT is implement-ed in this work. With the help of this system, doctors in a specialty hospital can monitor the distant patient in a rural area through PHC. In this manner, symptoms can be early detected and this helps the doctors to give proper advice to physicians in PHC. The Electrocardiogram (ECG) is wirelessly transmitted from patient side to a laptop in PHC which is configured as local server. The serial ECG data are then transmitted to the web server. Website www.ecgtrack.in is created and hosted with server so that doctors can view patientâ€™s ECG after log-ging on to the web site. Doctor can view the ECG of patients with three previous recordings. Multiple patient ECG from rural areas can be viewed by the doctor in the specialty hospital in real time and can make effective diagnose. This is a reporting of an emerging research work in this area.Â Â